Nonpolarizing guided-mode resonance filter with high tolerance of conical angle. (4th July 2018) - Ren, Zhibin; Sun, Yahui; Hu, Jiasheng; Lin, Zihao; Zhang, Kaipeng
Abstract: A tunable one-dimensional (1D) nonpolarizing guided-mode resonance filter (GMRF) with high peak efficiencies, narrow spectral linewidths, and low sideband reflections is experimentally demonstrated. The GMRF composed of a 1D grating and two waveguide layers on a glass substrate is designed with rigorous coupled-wave theory. The grating structure of the GMRF is patterned by interference lithography with two ultraviolet laser beams. The reflection resonance wavelengths of nonpolarizing spectra of the GMRF sample with period of 481.9 nm are tuned from 836.6 to 866.3 nm by rotating the angle of incidence. The measured full width at half-maximums of the reflection peaks located at 836.6, 844.1, 851.8, 858.4, and 866.3 nm are 8.1, 8.9, 9.0, 8.6, and 9.4 nm, respectively. The corresponding sidebands of the measured spectra are below 0.2. Moreover, the dependence of the nonpolarizing effect on the conical angle is studied to consider the mounting tolerance. The measured results show that the transmission and reflection spectra of two nonpolarizing GMRFs are insensitive to the conical angle. Compared with previous reported 1D nonpolarizing GMRFs, the tolerances of conical angle of the fabricated structures are remarkably enhanced.